The Last 41.000 Years Fluctuation in Atmosperic CO2 Concentration Inferred from The Changes in Oxygen and Carbon Stable Isotopes Ratios of The Marine Sediment - Wahyudi Wahyudi; Masao Minagawa (EKSPLORIUM, 2012)
The past atmospheric CO2 concentrations were reconstructed based on the results of measurements of stable oxygen and carbon isotopic ratios of fossil foraminifer and total organic carbon contained in marine sediment taken from the Okinawa Trough, East China Sea. In this study, we utilized two models of Popp et al and Rau et al. for the reconstruction. The results show that the whole trends of the changes in CO2 concentrations are very similar, even when it is compared to the atmospheric CO2 concentration of air trapped in ice core from southern pole. Changes in atmospheric CO2 concentrations are interpreted as a consequence of fluctuation in ocean surface water utilization of CO2 by marine organism and those are closely related to glacial-interglacial (cold-warm) fluctuations between maximum and minimum values through most Quaternary. Rekonstruksi terhadap perubahan konsentrasi CO2 yang terkandung dalam udara telah dilakukan berdasarkan hasil pengukuran rasio isotop stabil oksigen dan karbon dalam fosil foraminifera dan total karbon organik yang terkandung dalam sedimen dasar laut dari Okinawa Trough, Laut Cina Timur. Dalam studi ini, dipakai model dari Popp et al. dan Rau et al. untuk rekonstruksi. Hasil studi menunjukkan bahwa kedua tren dari perubahan kandungan CO2 udara sangat mirip, bahkan bila dibandingkan dengan kandungan CO2 udara yang terperangkap dalam inti es di Kutup Selatan sekalipun. Perubahan kandungan CO2 udara diinterpretrasikan sebagai akibat fluktuasi konsumsi CO2 di permukaan air laut oleh mikro-organisme yang juga sangat erat hubungannya dengan fluktuasi glasial-interglasial (dingin-panas) antara suhu udara bumi maksimum dan minimum sepanjang masa Kuarter.